Making Room for Everyone’s Talent - Huijpen, Kim (Septentrio Conference Series, 2021)
See RECORDING. Current societal challenges demand more cooperation and a multidisciplinary approach from scientists. Putting into practice the shared ambition in Dutch academia requires a modernisation of the system of Recognition & Rewards. The modernisation should improve the quality of each of the key areas in academia: education, research, impact, leadership and (for university medical centres) patient care. Why do we think a change in recognition and rewards is needed? We see a mismatch between what we deem important in academic work and what we reward academic staff for. Careers depend heavily on research performance, which is measured by a limited number of criteria. We need a better balance in how we recognize and reward academics to help us achieve excellent education, research, impact, and leadership, as well as the highest level of patient care in our university medical centres. We want to make Room for everyone’s talent! In the Dutch Recognition & Rewards programme we work in cooperation with all Dutch research universities, university medical centres, reputable research institutes, the Royal Academy, and research funders. We aim for a healthy and inspiring environment for all our staff, where all talents are valued. In this presentation I will explain what we want to change in academic career assessment in the Netherlands, and how we hope to initiate the desired cultural change. This change is a fundamental change of beliefs, not just a change in the rules of the game. To achieve this, a broad dialogue in academia is needed. We think that sharing best practices and experimenting will initiate the desired movement. Every university and research organisation in the Netherlands has set up a high-level Recognition & Rewards committee. The various committees are working enthusiastically to stimulate the intended culture change at an institutional level. There is a great and inspiring diversity of approaches. Experimenting, inspiring, co-creating, sharing best practices, and learning from each other are central in the joint programme. At a national level, we also monitor the commonality and ensure connections between the developments at the universities, university medical centres, research institutes, and research funders. We are aware that the Netherlands is only a very small country. We cannot change academic career assessment on our own. We need to work together all over the world to change the recognition and rewards of academics. We hope you are curious, critical, and open about your concerns and become involved!